Pemetaan Pura Tri Kahyangan Menggunakan Metode Visualisasi Data (Studi Kasus: Kecamatan Kerambitan,Tabanan, Bali) - Putu Dipta Ferdiana; I kadek Andy Asmarajaya; I Putu Mahendra Adi Wardana (RESI : Jurnal Riset Sistem Informasi, 2026)
The mapping of Pura Tri Kahyangan in Kerambitan District, Tabanan Regency, is still carried out conventionally, which complicates access to accurate spatial information for the public and stakeholders. This study aims to provide spatial data visualization of Pura Tri Kahyangan by utilizing Geographic Information System (GIS) technology based on digital maps. The method used is descriptive quantitative, with data collection techniques including observation, interviews, documentation, and literature studies. The results show that digital mapping using GIS can present the distribution of temple locations along with their supporting attributes interactively through a visualization dashboard. The implementation of this technology enhances the efficiency of information delivery, supports cultural preservation, and serves as a foundation for decisionmaking in temple management. Therefore, digital mapping is a strategic solution to provide accessible and informative spatial data.